KECANDUAN GADGET DAN INTERAKSI SOSIAL SISWA DI SEKOLAH SMK MUHAMMADIYAH 2 PEKANBARU - Anandio, Ken; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : Gadget Addiction and Student Social Interaction at SMK Muhammadiyah 2 Pekanbaru School. Based on the title can be taken understanding that researchers want to know the social interaction of students who are addicted to gadgets. The purpose as follows: 1) To know the picture of student behavior addicted gadgets. 2) To find out the social interaction of students in SMK Muhammadiyah 2 Pekanbaru school. The operational definitions of Griffiths (2000) and (Soekanto, 2009) include: the following indicators of addiction: 1) Salience, 2) Mood Modification, 3) Conflict, 4) Withdrawal, 5) Relapse, 6) Tolerance. While the social interaction indicators as follows: 1) Direct and indirect conversation, 2) Understanding, 3) Open, 4) Empathy, 5) Two-way message, 6) Imitation, 7) Suggestion, 8) Sympathy. Populsi this research is 31 student addicted gadget. Samples of 31 students are addicted to gadgets. The data retrieval technique is a saturated sample. Data collection techniques used questionnaires. Data analysis using percentage technique. The results of this study show: 1) students have a high addiction gadget also has a high social interaction. 2) Addiction of gadgets to students of SMK Muhammadiyah 2 Pekanbaru dominant to Salience. 3) The social interaction of students in schools that are addicted to gadgets is in the high category. Students have a sense of empathy and sympathy among their friends in school. Recommendations: 1) To the SMK Muhammadiyah 2 Pekanbaru school to be able to guide and pay attention to students in school. 2) To the students are expected to be more wise in the use of gadgets.Keywords : Gadget Addiction and Social Interaction